MODEL TEMPERATUR UNTUK PENDUGAAN EVAPORASI PADA STASIUN KLIMATOLOGI BARONGAN, BANTUL - , FEBRIYAN RACHMAWATI, Dr. H. Suyono, M.S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
the evaporation can be done directly by using the evaporation pan class A. The objectives of this research are to determine the correlation between temperature and evaporation Class A pan in Barongan climatology station, get an equation of evaporation prediction model based on the temperature data (temperature models) in Barongan climatology station on 2000-2004 and applied the equation in other places. Correlation analysis and making temperature model with type polynomial regression analysis (quadratic) using temperature data and pan evaporation data in Barongan climatology station. Requirements of the data are selected on a sunny day (no rain), data of average temperature per day is singular so th pair of temperature data for the same value sought by calculating the average value of the class A pan evaporation per day (mm/day) and a paired data of temperature and evaporation pan should be normally distributed. Then the temperature model was tested by calculate the value of R2, r and RMSE to determine the best model. The recommended model can be applied in other climatological stations with correction rate and compatibility test. The result of this research showed that the correlation between temperature and evaporation pan is strong, itâs mean that the amount of evaporation pan can be predicted using the temperature data. Equation of the recommended temperature model is E0 = 0.013T2 - 0.318 T + 4.216. That temperature model can be applied in other places except Barongan climatology station with the correction rate 0.516.